The Challenges and Role Played among Workers of Department Human Resources Management towards Industry 4.0 in SMEs - Ismail, Fadillah; Abdul Kadir, Adibah; Asad Khan, Muhammad; Pei Yih, Yuen; Ali Hassen Humeed Al Hosaini, Adnan (KnE Social Sciences, 2019)
From smartphones to shrewd refrigerators, innovation has assumed a huge job in progressing most regions of our regular daily existences, yet it is additionally changing the universe of industry. Industry 4.0 is the imprint given to the moderate mix of conventional assembling and modern practices with the non-yielding mechanical world around us. Industry 4.0 is certainly not another development, nor is it a business discipline, anyway another approach to manage to achieve results that were not possible ten years back gratitude to the headways in innovation. To do so, first thing first, it is essential to determine the challenges are faced, and roles are played among workers of Human Resources Management (HRM) towards industry 4.0 in manufacturing SMEs. The study is intended to identify workers of HRM perform the challenges and tasks by randomly select 100 respondents from 50 manufacturing SMEs listed on SME Corp. State Office Perak within Menglembu, Perak. The present study provides a contribution to the area of industry 4.0, among the manufacturing sector of SMEs. The findings of this study show that the adoption of sector 4.0 influences all of the challenges which are lack of skilled workforce training and aging society later retirement. Besides that, all of the roles should play by HRM that SMEs can gain when they start to embrace industry 4.0, which is useful for workers. Keywords: industry 4.0, human resources management (HRM), challenges, roles